Determination of crack tip stress intensity factors by singular Voronoi cell finite element model. (15th June 2018) - Zhang, Rui; Guo, Ran
Abstract: A singular Voronoi cell finite element model (SVCFEM) is proposed for estimation of the mixed-mode stress intensity factors (SIFs) of crack tip in this paper. Formulation of a singular Voronoi cell finite element is based on a modified complementary energy principle. To satisfy the stress singularity at the crack tip, we enrich stress solution in assumed stress hybrid model. In addition to polynomial and reciprocal terms, singular stress terms of Williams expansion are added for elliptical crack to capture crack-tip stress concentrations. After obtaining the stress, SIFs of model I and model II were calculated using linear least-squares method. Comparisons of SVCFEM solution with analytical solution for crack are made to demonstrate the efficiency of SVCFEM.